The Relationship of Hadith Style to the Social Society of the Nusantara: A Study on Qami 'Al-Tughyan by Nawawi Al-Bantani - Pangestu, Perdana Putra (International Journal Ihya' 'Ulum al-Din, 2021)
One of the nusantara scholars with famous work inscriptions is Nawawi al-Bantani. These works are recorded in a multidisciplinary scope, one of which is Qami 'al-Tughyan. The significance of this research lies in the influence of environmental factors of Nawawi in the nusantara which have an influence on the style of writing, especially in the field of hadith. This study aims to reveal the facts of causality with the orientation of the literature analysis surrounding Nawawi's notes in compiling the Qami' al-Tughyan. The author will take an inductive qualitative approach by conducting a literature review through related literatures, derived from the object variables in the first ten sections (syu'bah) of the book Qami 'al-Tughyan. Then, the data will be explored in order to produce comprehensive and optimal research results. This research proves that the work recording model used by Nawawi is a causal representation of the situation in the nusantara, especially with regard to the practice of imperialism towards the indigenous people.